2004
DOI: 10.2466/pr0.94.1.195-207
|View full text |Cite
|
Sign up to set email alerts
|

Meaning of Work among a Sample of Kuwaiti Workers

Abstract: The study tested the meaning of work among 340 Kuwaiti workers in the public sector. A questionnaire was constructed to measure meaning of work by drawing 46 items from existing scales and from the meaning of work literature. They were put together, translated into Arabic, and adapted to be relevant to Kuwaiti society. Analysis showed the developed scale has acceptable reliability and validity coefficients for Kuwaiti workers. Also, Kuwaiti workers gave priority to extrinsic rewards from work, then intrinsic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
(25 reference statements)
0
2
0
3
Order By: Relevance
“…Super explains this phenomenon by the fact that people with higher occupational status have more control over their work schedules and activities and are, thus, more focused on work. A study by Hasan (2004), conducted among Kuwaiti workers, confirmed that higher occupational status was associated with higher work centrality. Finally, the earlier referenced study by Sousa-Posa and Sousa-Posa (2000) suggests that educational achievement tends to be negatively correlated with job satisfaction.…”
Section: Discussionmentioning
confidence: 92%
“…Super explains this phenomenon by the fact that people with higher occupational status have more control over their work schedules and activities and are, thus, more focused on work. A study by Hasan (2004), conducted among Kuwaiti workers, confirmed that higher occupational status was associated with higher work centrality. Finally, the earlier referenced study by Sousa-Posa and Sousa-Posa (2000) suggests that educational achievement tends to be negatively correlated with job satisfaction.…”
Section: Discussionmentioning
confidence: 92%
“…Salah satu bagian yang penting dalam hidup manusia adalah bekerja dan pada umumnya manusia menghabiskan banyak waktunya di tempat kerja (Hasan, 2004). Hasil survei yang dilakukan oleh firma konsultan Tower Perrin (dalam Scroggins, 2008) menunjukkan bahwa kebermaknaan kerja sekarang dipandang oleh para pekerja sebagai hal yang lebih bernilai jika dibandingkan dengan hadiah eksternal yang diterima.…”
Section: Pendahuluanunclassified
“…Kebermaknaan kerja sendiri telah banyak diteliti namun demikian rata-rata penelitian tersebut dilakukan di Amerika utara dan Eropa selaras dengan pendapat Nystedt, Sjoeberg dan Haegglund (1999) yang menyebutkan sebagian besar penelitian tentang sikap kerja termasuk kebermaknaan kerja dilakukan di Amerika Utara dan Eropa, yang hasilnya tidak dapat digeneralisasikan lintas negara dengan kondisi industri, ekonomi, budaya serta tradisi yang berbeda, tanpa beberapa pengujian empiris. Sedangkan Hasan (2004) Laki laki Perempuan Asal Pemahaman Partisipan Atas Peran Suami dan Istri L1: "...asline kan ngene wong wedok neng omah, wong lanang kerjo ngunu ki wes ono ket jaman leluhur mbak..., di agama juga gitu ta mbak" P1: "...saya juga tetap akan menjalankan peran saya sebagai konco wingking walaupun berarti saya harus bekerja lebih keras ya mbak, saya harus konsisten karena saya diijinkan bekerja" L2: "...secara takdir atau kodrat istri memang tidak bekerja dia harus mengurus rumah tangga dan suami yang bekerja, itu sudah ketetapan-Nya..." P2:"...Memang kerja tugas suami tapi saya akan kerja lebih keras biar bisa kerja. Kerjaan rumah sama anak beres, saya tidak akan mengabaikan tugas saya, Emang tidak ada yang memberitahu saya, tapi semua orang kan begitu, kalau kita lihat kan dari mbah-mbah kita sudah ada" L: "Pada waktu akad nikah laki-laki dikasih penjelasan dari naif tanggung jawab seorang suami itu memberi nafkah dan mencukupi kebutuhan keluarga istri dan anak-anak" P3: "Hidup di masyarakat kan gitu, perempuan tidak boleh melebihi suami dalam penghasilan dan pendidikan karena, contone ngene mbak kerja cari uang kan tugas suami, perempuan atau istri bagian rumah, bisa kerja kalau suami ijinkan.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Meaningful work is central to subjective well-being and job satisfaction of most adults in contemporary human societies (Super & Sverko, 1995). Numerous studies of work-related values and beliefs were conducted around the world during the past two decades (Furnham, 1990;Furnham & Rajamanickam, 1992;Hasan, 2004;Kuchinke, Kang, & Oh, in press;Lundberg & Peterson, 1994;MOW International Research Team, 1987;Niles, 1999). Most of these studies were based on an implicit assumption that, in addition to cultural factors, socioeconomic conditions play a key role in shaping societal perceptions of the meaning of working.…”
mentioning
confidence: 99%